Pengaruh Kualitas Layanan Website Menggunakan Metode Webqual 4.0. Terhadap Kepuasan Pemustaka pada Dinas Perpustakaan dan Kearsipan Provinsi Sulawesi Selatan - Rusmana, Ayu Warasari; Burhanuddin, Burhanuddin; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the effect of Website Service Quality with the Webqual 4.0 Method on User Satisfaction at the Library and Archives Service of South Sulawesi Province. The type of research used is quantitative research, with descriptive type. The data sources used in this study are primary data sources and secondary data. Data collection techniques using observation and questionnaires with the number of respondents as many as 50 people who are determined by the sampling technique refers to the table Krejcie and Morgan. Respondent data were analyzed by multiple linear regression using the SPSS version 25 application. The results of this study indicate that partially the website service quality variable has a positive and significant influence on user satisfaction, namely the Usability indicator (X1.1) of 36.4% is low, and Information Quality (X1.2) of 48.6% is moderate, and Service Interaction Quality (X1.3) of 31.4% is low. Then simultaneously the influence of website service quality using Webqual 4.0 at the Library and Archives Service of South Sulawesi Province on user satisfaction is 48.1% or categorized as moderate.